1889 Tex. Gen. Laws 36, Malicious Mischief, ch. 40, art. 683b - (:unkn) unknown (My University, 1889)
That any person who shall willfully or maliciously throw a stone or other missile or fire a gun or pistol at or into any coach or passenger car of a moving railway train, shall be deemed guilty of a misdemeanor, and on conviction thereof shall be fined in any sum of not less than twenty-five dollars and not more than one thousand dollars.
Keywords: DISCHARGE